Urban Memory in Halabje and the Reflection of Urban Memory in City - Jaff, Asmaa Ahmed Mustafa; Alkan Bala, Havva (ICONARCH International Congress of Architecture and Planning, 2017)
The city is a place of memory. Buildings, monuments, roads, squares, green areas are important elements for the city. However, we cannot talk about soul of the city without urban memory. Urban memory is as a kind of collective memory that is constituted by individuals’ experiences within the place itself and through its history and social environment. Every society has a social memory. This social memory all events of human history they have lived hold in memory, record and transmit to future generation. The place of memory in social life and political culture has called attention to the various struggles over remembering and forgetting the past. The events the impact on people coming to city and by past events make empathy, allows to living in the moment. Wars create a big crack on people’s and their life as well as the city. This research is about collective urban memory and the politics of urban space in case of Halabja. The meaning of Halabja totally dealing with urban memory and urban space in the past and even today. It’s very important to issue this criteria and preserving memory that by developing of public memory on urban place, to know the city of Halabja, the effects of urban memory left in this city examine in detail and the people living there city with social relation was investigated. The chemical attacks and its effect on urban life, urban memory has been cleared out.